A Study on Traditional and Social Approaches in the Novels of R. K. Narayan: Exploring Traditional and Social Themes in R.K. Narayan's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Malgudi is an innovative area made by Narayan in his books and short stories. It shapes the setting for the greater part of Narayan's works. The endeavor in this Research Paper is made to appear, how through the arrangement of Malgudi books Narayan presents the social qualities standards, mores which have been in presence and still keep on playing a noteworthy part in molding the lives of Hindu individuals. The critical family topics like Marital loyalty, spouse wife and father-child relationship, parental love and absence of correspondence between the old and the youthful age and so forth all are perfectly bargained by Narayan in his books. R. K. Narayan, one of the best Indian English authors and an incredibly famous artistic figure of the twentieth century, is among the establishing fathers of Indian English fiction. Alongside Raja Rao and Mulk Raj Anand, he not just introduced the novel frame in Indian English writing yet in addition characterized the zone in which the Indian novel was to work so far its topic and portrayal are concerned. Every one of these three authors — called the considerable trio - utilized his own particular rendition of English, liberated from foggy taste of Britain, and exchanged it to another setting of splendid light and purged heart. Among these Indian English authors R. K. Narayan is incomparable and the best since his fiction uncovers changed measurements of Indian life, custom and ethos delineated or spoke to through his one of a kind individual ability.